International Strategies adn Techniques for Future Local Government - Prohl, Marga (Bertelsman Foundation Publishers, 1997)
Owing to the ongoing financial crisis, the growing demands of citizens put to public services and the desire of employees towards more self-fulfillment, far -reaching changes must be made in municipal administrations. An increasing number of cities in Germany and abroad are experimenting with new concepts of management and organization in an attempt to reform their administrations and convert them into modern public service companies. In order to compile the various experinces with reform made it an international level as well as to explore and document innovative examples worlwide, the Bertelsmann Fpuncation has founded the International network "Cities of Tomorrow"